In Vitro Antioxidant Properties of Three Varieties of Allium sativum L. Extracts - R. T. Narendhirakannan; K. Rajeswari (E-Journal of Chemistry)
Many herbs possess antioxidant ingredients that provide efficacy by additive or synergistic activities. Allium sativum L. is a strong astringent, used for the treatment of liver and spleen diseases, rheumatism and tumors. The antioxidant activities of different concentrations of ethanolic extracts of garlic bulb of three varieties were determined by the four assays i.e. DPPH radical scavenging assay, reducing power ability, hydrogen peroxide scavenging assay and total antioxidant capacity. Due to its natural origin and potent free-radical scavenging ability, Allium sativum L. could be used as a potential preventive intervention for free radical-mediated diseases.